Synthesis, liquid crystalline behaviour and structure–property relationships of 1,3-bis(5-substituted-1,3,4-oxadiazol-2-yl)benzenes - Mabrouki, Afef; Fouzai, Malek; Soldera, Armand; Kriaa, Abdelkader; Hedhli, Ahmed (Beilstein Journal of Organic Chemistry, 2020)
Two series containing 1,3-bis(1,3,4-oxadiazol-2-yl)benzene as a rigid core (RC) and alkyl or perfluoroalkyl as terminal chains were synthesized and characterized. Liquid crystal properties of the synthesized compounds have been investigated by polarizing optical microscopy, differential scanning calorimetry and X-ray diffraction techniques. Conformation effects of the synthesized products on the dipole moments were also investigated.
Keywords: dipole moment; fluorine; liquid crystal; oxadiazole